Energetic particle forcing of the Northern Hemisphere winter stratosphere: comparison to solar irradiance forcing - Seppälä, Annika; Clilverd, Mark A. (Frontiers in Physics, 2014)
Variation in solar irradiance is considered an important factor in natural climate forcing. Variations in the solar UV in particular are now regarded as a major source of decadal variability in the stratosphere, influencing surface climate through stratosphere-troposphere coupling. However, by analyzing meteorological re-analysis data we find that the magnitude of the solar controlled energetic particle forcing signal in stratospheric zonal mean zonal winds and polar temperatures is equivalent to those arising from solar irradiance variations during the Northern hemisphere polar winter months. We find that energetic particle forcing drives warmer polar upper stratospheric temperatures from early winter leading to an anomalously strong polar night jet via modulation of the vertical temperature gradient. By midwinter the stratosphere-troposphere coupling pathway becomes analogous to the solar UV impact at high latitudes. This not only highlights the importance of the energetic particle forcing contribution to stratospheric circulation, but enables us to understand the pathways responsible for the previously reported energetic particle forcing impacts on the troposphere in terms of the coupling of solar UV forcing to dynamics in the latter part of the winter.